1980
DOI: 10.1002/jclp.6120360215
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of black and white children's WISC/WISC‐R differences

Abstract: Administered the WISC and WISC-R to 20 white child psychiatric out-patients in a counterbalanced design. The white Ss' WISC/WISC-R differences were compared to equivalent data obtained from black children (Munford, 1978). For the white Ss, no differences were found between WISC and WISC-R Verbal, Performance, and Full Scale IQs, whereas black children scored significantly lower on the WISC-R than on the WISC on all three IQ measures. These findings indicate increased cultural bias in the WISC-R, despite appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Radiolabeling studies with core-defective mutants (Re chemotype) and epimerase-defective mutants ( g a l 0 have led to the conclusion that the bands represent LPS constituents with increasing numbers of 0-side chains [1,5,6]. The LPS with the greatest mobility is the Re chemotype, with those of intermediate core lengths or semirough (one 0-side chain) having intermediate mobilities [2,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiolabeling studies with core-defective mutants (Re chemotype) and epimerase-defective mutants ( g a l 0 have led to the conclusion that the bands represent LPS constituents with increasing numbers of 0-side chains [1,5,6]. The LPS with the greatest mobility is the Re chemotype, with those of intermediate core lengths or semirough (one 0-side chain) having intermediate mobilities [2,5].…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation of LPS SDSjPAGE patterns has been facilitated by the use of radiolabeling techniques with LPS mutants such as incorporation of isotopes into the 0-side chain, the core or the lipid A components and subsequent analysis of the distribution of isotopes in LPS SDSjPAGE patterns [2,5,6].…”
mentioning
confidence: 99%
“…Additionally, significant differences in subtest scores between African Americans and Caucasians have been found. Ethnically diverse children displayed subtest score discrepancies on several Wechsler subtests from the WISC and WISC-R (Munford, Meyerowitz, & Munford, 1980). Specifically, Caucasian children preformed approximately one standard deviation, or 2-4 points, higher than African American children on the Information, Comprehension, Arithmetic, Object Assembly, Picture Arrangement, and Block Design subtests.…”
Section: Jensen Reported Most Standardized Tests Of Intelligence Usmentioning
confidence: 98%
“…Ethnically diverse children also show similar subtest score discrepancies. Specifically, the Information, Comprehension, Arithmetic, Object Assembly, Picture Arrangement, and Block design subtests of the WISC and the WISC-R yielded differences between two to four points, with the largest difference displayed on Picture Arrangement and Object Assembly (Munford, Meyerowitz, & Munford, 1980). Furthermore, the research indicated an increasing gap in subtest performance between the revisions and researchers questioned the utility of the WISC-R with African American children.…”
Section: Racial Differences In Intelligencementioning
confidence: 99%
See 1 more Smart Citation